The effect of water-side scale formation to heat transfer process and boiler efficiency - Faiq Nur, Abdul Halim (2007)
Boiler's role in steam generation industry has long been plagued by the scale formation problem. The scale problem has been primary cause for boiler shutdown as retardation of heat due to the presence of scale cause the tube to be overheated; hence tube rupture occurs in gradual. Besides, scale formation is also triggering factor to various boiler problems. The likes of increased fuel bill due to decrease in efficiency, increased cleaning time and cleaning cost, and reduced working life of a boiler are among the problems originated from scaling problem. The objective of this project is to analyze how efficiency of a boiler unit is affected by the scale formation problem. The outcome of this project will underscore the importance of having clean boiler tube in order to achieve highest possible boiler efficiency. Besides, this project aims to create awareness among boiler operators on the importance of supplying highest quality of feedwater to the boiler as to avert scale built-up in the tube. As scaling problem is inevitable due to the presence of impurities in feedwater, it can be minimized by implementing best and suitable water treatment method.